Parallel and Differential Contributions from Language and Image in the Discourse Representation of Picturebooks - Abusch, Dorit; Rooth, Mats (Proceedings of Sinn und Bedeutung, 2023)
This paper proposes an account in Discourse Representation Theory of children’s picture books, combining language and image. The focus is on works where the language and image have a different pragmatic status, with the linguistic part of the book being prosaic and understated by comparison with the pictorial part. The effect of wryness and incongruity is analyzed in pragmatic terms.